2006
DOI: 10.1111/j.1532-5415.2006.00894.x
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Brain Injury in Older Adults: Epidemiology, Outcomes, and Future Implications

Abstract: Traumatic brain injury (TBI) is a significant problem in older adults. In persons aged 65 and older, TBI is responsible for more than 80,000 emergency department visits each year; three-quarters of these visits result in hospitalization as a result of the injury. Adults aged 75 and older have the highest rates of TBI-related hospitalization and death. Falls are the leading cause of TBI for older adults (51%), and motor vehicle traffic crashes are second (9%). Older age is known to negatively influence outcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

30
375
2
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 514 publications
(422 citation statements)
references
References 58 publications
30
375
2
15
Order By: Relevance
“…Traumatic brain injury (TBI) in older adults is a significant public health issue, with, for example, adults in the US aged 75 and older having the highest rates of TBI-related hospitalization and death (Thompson et al, 2006). Unfortunately, increasing age is strongly associated with a poor prognosis both in experimental trauma models and following TBI in humans (Livingston et al, 2005;Onyszchuk et al, 2008;Rothweiler et al, 1998;Sendroy-Terrill et al, 2010;Susman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traumatic brain injury (TBI) in older adults is a significant public health issue, with, for example, adults in the US aged 75 and older having the highest rates of TBI-related hospitalization and death (Thompson et al, 2006). Unfortunately, increasing age is strongly associated with a poor prognosis both in experimental trauma models and following TBI in humans (Livingston et al, 2005;Onyszchuk et al, 2008;Rothweiler et al, 1998;Sendroy-Terrill et al, 2010;Susman et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…T raumatic brain injury (TBI) is a significant problem in senior citizens, with old age being associated with a poor recovery from brain injury (Hukkelhoven et al, 2003;Livingston et al, 2005;Thompson et al, 2006). The poorer prognosis has prompted some investigators to advocate a more conservative approach in elderly patients with moderate and severe TBI (Gan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that falls are the most common cause of TBI in older adults since approximately 10% of falls in older people result in injuries such as TBI as per Thompson et al 31 . Other studies have confirmed that falls were the leading mechanism of TBI for older adults, accounting for 51% of cases as per Langlois et al 32 .…”
Section: Gender Distribution 1st Qtr 2nd Qtrmentioning
confidence: 99%
“…TBI is responsible for more than 80,000 emergency department visits by persons aged 65 years or older each year in the United States, and this group has the highest rates of TBI-related hospitalization and death. 29) The Japan Neurotrauma Data Bank found significant differences in mortality rates between patients aged 65-69 years and patients aged 70-74 years. 31) Elderly individuals, 65 years of age or older, account for a disproportionate number of TBI cases and have a staggering incidence of morbidity and mortality.…”
Section: Introductionmentioning
confidence: 99%